The problems of the medical terminology (on the base of German) - J Baghana (Russian journal of linguistics: Vestnik RUDN, 2013)
The article discusses the problems of the medical terminology such as synonymy, polysemy, eponymy and others, as well as different opinions about the phenomena of linguistic character of medical terminology.